Desire where it should not be: monks, love and sex - Albrecht Berger (Anales de Filología Clásica, 2018)
From the beginning of monasticism to our days, monks were always exposed to sexual temptations, either provoked by women or men from outside, or by fellow monks and underage novices from inside the monasteries. A special problem in the Byzantine age was also posed by the presence of eunuchs. While early monastic rules try to suppress homosexual behavior by strict regulations and threats of punishment, intimate relationships among monks are later widely accepted and even institutionalised.